Impact of simulated micro-scotomas on reading performance in central and peripheral retina. (June 2019) - Krishnan, Arun kumar; Queener, Hope M.; Stevenson, Scott B.; Benoit, Julia S.; Bedell, Harold E.
Abstract: Observers with central field loss typically fixate within a non-foveal region called the preferred retinal locus, which can include localized sensitivity losses, or micro-scotomas (Krishnan and Bedell, 2018). In this study, we simulated micro-scotomas at the fovea and in the peripheral retina to assess their impact on reading speed. Ten younger (<36 years old) and 8 older (>50 years old) naïve observers with normal vision monocularly read high and/or low contrast sentences, presented at or above the critical print size for young observers at the fovea and at 5 and 10 deg in the inferior visual field. Reading material comprised MNREAD sentences and sentences taken from novels that were presented in rapid serial visual presentation (RSVP) format. Randomly distributed 13 × 13 arc min blocks corresponding to 0–78% of the text area (corresponding to ∼0–17 micro-scotomas/deg 2 ) were set to the background luminance to simulate micro-scotomas. A staircase algorithm estimated maximum reading speed from the threshold exposure duration for each combination of retinal eccentricity, contrast and micro-scotoma density in both age groups. Log10 (RSVP reading speed) decreased significantly with simulated micro-scotoma density and eccentricity. Across conditions, reading speed was slower with low-compared to high-contrast text and was faster in younger than older normal observers. For a given eccentricity and contrast, a higher density of random element losses maximally affected older observers with normal vision. These outcomes may explain some of the reading deficits observed in older observers with central field loss.